2019
DOI: 10.1002/jcph.1401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pharmacokinetic Properties of Naloxone Following the Use of FDA‐Approved Intranasal and Intramuscular Devices Versus a Common Improvised Nasal Naloxone Device

Abstract: For more than a decade, first responders and the general public have been able to treat suspected opioid overdoses using an improvised nasal naloxone device (INND) constructed from a prefilled syringe containing 2 mg of naloxone (1 mg/mL) attached to a mucosal atomization device. In recent years, the U.S. Food and Drug Administration (FDA)-approved Ezvio, an autoinjector that delivers 2 mg by intramuscular injection and Narcan nasal spray (2-and 4-mg strengths; 0.1 mL/dose) for the emergency treatment of a kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
(29 reference statements)
2
15
0
Order By: Relevance
“…Subsequent examination of patent records located data confirming only poor bioavailability (approximately 10% of dose administered) [82] and recent direct pharmacokinetic comparison of the improvised kits vs. the new concentrated naloxone nasal spray formulations found bioavailability of only approximately 20% with the improvised kits vs. more than 40% with the new concentrated naloxone sprays [83]. Nevertheless, the evident successful reversals of opioid overdoses with these improvised kits [7577] should raise questions about the dose necessary for layperson reversal which, in these instances, appears to have been achieved with much lower absorbed concentrations of naloxone.…”
Section: Pharmacokinetics and The Development Of New Non-injectable Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent examination of patent records located data confirming only poor bioavailability (approximately 10% of dose administered) [82] and recent direct pharmacokinetic comparison of the improvised kits vs. the new concentrated naloxone nasal spray formulations found bioavailability of only approximately 20% with the improvised kits vs. more than 40% with the new concentrated naloxone sprays [83]. Nevertheless, the evident successful reversals of opioid overdoses with these improvised kits [7577] should raise questions about the dose necessary for layperson reversal which, in these instances, appears to have been achieved with much lower absorbed concentrations of naloxone.…”
Section: Pharmacokinetics and The Development Of New Non-injectable Nmentioning
confidence: 99%
“…Most importantly, these high-concentrate sprays deliver therapeutic doses (0.4–2.0 mg) in a single 0.1-mL spray, and a second spray gives a proportionate rise in serum concentrations. In contrast, dilute nasal spray (2 mg/2 mL) administered via the MAD only had 11–20% absolute bioavailability, implying that a sub-therapeutic dose of approximately 0.2–0.4 mg was delivered [74, 82, 83]. A recent study confirmed that, even after two administrations, dilute nasal spray (2 mg/2 mL, administered via a MAD) failed to achieve naloxone plasma concentrations comparable to concentrate nasal sprays (2 mg/0.1 mL, 4 mg/0.1 mL) at any time [83].…”
Section: Pharmacokinetics and The Development Of New Non-injectable Nmentioning
confidence: 99%
“…One variable that was considered but reluctantly excluded was a naloxone dose variable. Whilst it would have been theoretically possible to convert the naloxone given at each overdose into a standardised dose, this would likely have produced misleading data as the amount of naloxone absorbed from different kits and formulations varies significantly (McDonald et al, 2018;Krieter et al, 2019). After several attempts to calculate a variable for 'naloxone dose absorbed', the team were not satisfied that the results were sufficiently reliable and so decided to use variables for 'intramuscular versus intranasal administration' and 'one naloxone dose versus more than one naloxone dose' instead.…”
Section: Variable Construction-preliminary Readings Of the Interview Transcriptions Andmentioning
confidence: 99%
“…1,2 There are only a few previous studies describing the pharmacokinetics of intranasal naloxone, and in these, the concentration of naloxone used is higher than in the commonly marketed solution. [3][4][5][6] In children, there are only case reports on the use of intranasal naloxone. 7 Our group has previously shown that in adult healthy volunteers, intranasal administration of the commonly marketed solution of naloxone, 0.4 mg/ml, has a bioavailability that is comparable to intramuscular injection.…”
Section: Introductionmentioning
confidence: 99%
“…Naloxone is often administrated intravenously, but there is a growing interest in the intranasal route, mainly in treating patients with opioid overdose 1,2 . There are only a few previous studies describing the pharmacokinetics of intranasal naloxone, and in these, the concentration of naloxone used is higher than in the commonly marketed solution 3–6 . In children, there are only case reports on the use of intranasal naloxone 7 .…”
Section: Introductionmentioning
confidence: 99%